Course Delivery Format, Global Openness, and Openness to Experience in International Business Classes. Issue 1 (2nd January 2020) - Chen, Jiun-Shiu; Mooty, Scott; Stevens, Jeffery; Brown, Barron
ABSTRACT: This research studies the impact of taking an international business course (IB) under both online and face-to-face methods on changes in the attitudinal construct global openness. This research also examines how the personality trait of openness to experience influences the change in the degree of global openness achieved by the students. Findings show that taking IB significantly increases students' degree of global openness in both online and face-to-face methods; however, the increase is greater with face-to-face students than online. By dividing the sample into both high versus low openness to experience and online versus face-to-face, findings show differences between the high and low openness to experience groups in both online and face-to-face courses. In face-to-face classes, the results showed that the low openness students increased their degree of global openness more than the high openness to experience students. The increase is not found to be significant with the online high openness group indicating that online IB education is less effective with high openness to experience students. The overall results suggest face-to-face teaching is more effective in making attitudinal changes than online teaching.